Ex facto oritur jus? Constituent Power and Legas Orders. Remarks on Hans Lindahl’s “Fault Lines of Globalization” - Pomarici, Ulderico (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
This paper aims at discussing and scrutinizing some theses constitutive of Hans Lindahl’s book Fault Lines of Globalization. Particular attention will be devoted, firstly, to the issue of boundaries, limits and fault lines and to the related question as to how one has to understand the distinction between a weak and a strong dimension of a-legality. As to the latter, a critical investigation will be deployed concentrating on the instance of secession. In the last section of the paper, I will discuss some cases in which the role of jurisprudential interpretation will emerge as extremely relevant for a thorough comprehension of legal orders’ transformation. Keywords: Lindahl, A-legality, Boundaries, Legal orders, Schmitt.